2019
DOI: 10.4103/ijciis.ijciis_40_19
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile and prolactin serum levels in men with type 2 diabetes mellitus: Old-new rubric

Abstract: Background:Prolactin (PRL) is involved in the regulation of glucose metabolism since high PRL serum levels are associated with low incidence of type 2 diabetes mellitus (T2DM). Therefore, the aim of the present study was to assess the metabolic effects of PRL on glucose homeostasis in men with T2DM.Methods:Eighty male patients with T2DM compared with 25 male healthy controls matched with patients for age and weight were divided into four groups: Group (A): patients with T2DM on metformin (n = 29), Group (B): p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Thus, untreated and long-standing hyperglycemia may lead to ALI through ischemic-reperfusion injury ( 22 ). Also noteworthy is the fact that hyperglycemia is associated with oxidative stress' induction and inflammatory mediators' overproduction, which together partake in the development of endothelial dysfunction and thrombosis due to alterations in both function and generation of antithrombin III ( 23 ). Taken together, these findings reveal that both COVID-19 and hyperglycemia interact in a vicious cycle leading to more complications and worse metabolic outcomes.…”
Section: Covid-19 and Hyperglycemiamentioning
confidence: 99%
“…Thus, untreated and long-standing hyperglycemia may lead to ALI through ischemic-reperfusion injury ( 22 ). Also noteworthy is the fact that hyperglycemia is associated with oxidative stress' induction and inflammatory mediators' overproduction, which together partake in the development of endothelial dysfunction and thrombosis due to alterations in both function and generation of antithrombin III ( 23 ). Taken together, these findings reveal that both COVID-19 and hyperglycemia interact in a vicious cycle leading to more complications and worse metabolic outcomes.…”
Section: Covid-19 and Hyperglycemiamentioning
confidence: 99%
“…T2DM represents 95% of all diabetes types and contributes to 5% of all mortalities under the age of 70 [ 23 , 24 ]. Genetic, epigenetic, environmental factors, obesity, smoking and male sex are the main risk factors involved in the development and progression of T2DM [ 25 , 26 ]. Particularly, aggregation of hIAPP is associated with the development of T2DM by inducing apoptosis and loss of pancreatic β cells in the islet of Langerhans [ 21 ].…”
Section: Role Of Hiapp In T2dmmentioning
confidence: 99%
“…In contrast, a longitudinal study comprised Chinese adults with hypertension illustrated that low furin levels were associated with a high risk of hypertension 28 suggesting a protective effect of furin. Similarly, a prospective study demonstrated that a deficiency of furin increases the risk for the development of abdominal obesity 29–31 . However, Ren et al 32 disclosed that furin through induction of inflammatory reaction and lipid dysmetabolism may promote the propagation of atherosclerosis and hypertension.…”
Section: Furin and Cardiometabolic Disordersmentioning
confidence: 99%
“…Similarly, a prospective study demonstrated that a deficiency of furin increases the risk for the development of abdominal obesity. 29 , 30 , 31 However, Ren et al 32 disclosed that furin through induction of inflammatory reaction and lipid dysmetabolism may promote the propagation of atherosclerosis and hypertension. These findings suggest a latent controversy regarding the role of furin in the development of cardiometabolic disorders.…”
Section: Furin and Cardiometabolic Disordersmentioning
confidence: 99%